2021
DOI: 10.1016/j.ajic.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Operating room air delivery design to protect patient and surgical site results in particles released at surgical table having greater concentration along walls of the room than at the instrument tray

Abstract: Highlights Modern air handling systems for operating rooms protect the patient and surgical team. Concentrations of air particles are greater along walls than at the instrument table. Fewer particles are found at the center of the operating room. Stepping 2 m away from patient would not protect personnel in operating rooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…These results pertaining to individual ORs are important because there are multiple interventions that could reduce surgical site infection that are applied according to the OR (e.g., capital equipment or ultraviolet-C germicidal lights used nightly). 3,[8][9][10][11][12][13][14][15][16][17][18] Even at a large teaching hospital with C Among the 11,958 combinations of date and room with at least one case lasting 196-290 min, those date and room combinations had a median [interquartile range (IQR)] of 2 [2-3] cases, 11.7% with one case. In contrast, among the 15,398 combinations with at least one case of the preceding quartile of duration (126 to 195 min), there were a median [IQR] of 3 [2-3] cases, 7.48% combinations with one case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results pertaining to individual ORs are important because there are multiple interventions that could reduce surgical site infection that are applied according to the OR (e.g., capital equipment or ultraviolet-C germicidal lights used nightly). 3,[8][9][10][11][12][13][14][15][16][17][18] Even at a large teaching hospital with C Among the 11,958 combinations of date and room with at least one case lasting 196-290 min, those date and room combinations had a median [interquartile range (IQR)] of 2 [2-3] cases, 11.7% with one case. In contrast, among the 15,398 combinations with at least one case of the preceding quartile of duration (126 to 195 min), there were a median [IQR] of 3 [2-3] cases, 7.48% combinations with one case.…”
Section: Discussionmentioning
confidence: 99%
“…8 For example, ORs differ in their numbers of air changes per hour, ceiling air diffuser designs, room geography, and types of airflow (e.g., laminar or turbulent). [9][10][11][12][13] Some ORs are designed with door locks and electronic signage to prevent main and inner core doors from being open at the same time. 14 Germicidal OR lighting can also be installed.…”
Section: Re ´Sumementioning
confidence: 99%
See 1 more Smart Citation
“… [34] However, data from mock surgical procedures suggested that stepping 2 m away from the operative field would “not” protect personnel in operating rooms (LoE 3b). [35] 4.2 Concentrations of air particles were found to be greater along OR walls than at the instrument table at the centre of the OR (LoE 3b). [35] Coupled with our results, the non-surgical OR personnel and anaesthetic machine should not only step ≥ 3 m away from the operative field, but also be far from the OR wall.…”
Section: Resultsmentioning
confidence: 99%
“… [35] 4.2 Concentrations of air particles were found to be greater along OR walls than at the instrument table at the centre of the OR (LoE 3b). [35] Coupled with our results, the non-surgical OR personnel and anaesthetic machine should not only step ≥ 3 m away from the operative field, but also be far from the OR wall. Instrument containers that are not necessary for the surgery should not be slid next to the walls (i.e.…”
Section: Resultsmentioning
confidence: 99%